Dissertation of Startup Finance and Risk Controls (Global Journal of Management and Business Research, 2020)
The Startup has become synonyms for the growth, entrepreneurial traits, vision, and futuristic approach. India has a healthy environment and acts as a game-changer, a longlasting impact on the economy and standards of living of any nation. Startups have grown in no time both in numbers and contribution wise in a job and revenues. This paper tries to conceptualize the phenomenon, i.e., "startup," and "Entrepreneurship" recognizes the challenges they might face. For the fashionable enterprise, assets in business activities are to support the operation of their overall funding and is that the foundation of sustainable management and financial risk. During this paper, the financial risks of business activities of new enterprises is being studied, the strategies to uplift the risk failure of startups offerings of government for encouraging innovative ideas of the young generation.
Keywords: entrepreneurship; pragmatic risks; mitigation; investments